2014
DOI: 10.1007/s00526-014-0748-3
|View full text |Cite
|
Sign up to set email alerts
|

Stability and instability of Ricci solitons

Abstract: We consider the volume-normalized Ricci flow close to compact shrinking Ricci solitons. We show that if a compact Ricci soliton (M, g) is a local maximum of Perelman's shrinker entropy, any normalized Ricci flow starting close to it exists for all time and converges towards a Ricci soliton. If g is not a local maximum of the shrinker entropy, we show that there exists a nontrivial normalized Ricci flow emerging from it. These theorems are analogues of results in the Ricci-flat and in the Einstein case [HM13,Kr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 37 publications
(31 reference statements)
1
37
0
Order By: Relevance
“…Moreover, S-linear instability implies ν-linear instability and further also ν-instability (see Definition 1.2 below). Then by Theorem 1.3 in [Kr15], (since Λ > 0) it also implies that g is dynamically unstable for the Ricci flow.…”
Section: Introductionmentioning
confidence: 89%
“…Moreover, S-linear instability implies ν-linear instability and further also ν-instability (see Definition 1.2 below). Then by Theorem 1.3 in [Kr15], (since Λ > 0) it also implies that g is dynamically unstable for the Ricci flow.…”
Section: Introductionmentioning
confidence: 89%
“…Hence, in the course of the proof of Theorem , we show that G2 has non‐integrable infinitesimal solitonic deformations. This can be compared with [, Theorem 1.5] where it is shown that the Fubini–Study metric on CPn has non‐integrable solitonic deformations for n2.…”
Section: Introductionmentioning
confidence: 94%
“…The relationship between Cao–Hamilton–Ilmanen's linear stability and dynamical stability for Einstein metrics with Λ>0 was made precise by Kröncke who built on earlier work by Sesum and Haslhofer and Müller . Proposition Let (M,gE) be a compact Einstein manifold satisfying Ricfalse(gEfalse)=ΛgE with Λ>0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, linear instability along a nonzero TT-tensor gives a non-trivial variation along which S has a local minimum. When E > 0, Theorem 1.3 in [Kro15] then implies that such an Einstein metric is dynamically unstable. Therefore, all linearly unstable Einstein metrics discussed in this paper are dynamically unstable, for example Einstein metrics investigated in Corollaries 1.3 and 1.4.…”
Section: Introductionmentioning
confidence: 99%